Preparation and Evaluation of a Profile Control Agent Base on Waste Drilling Fluid - Xiaoping Qin; Haiwei Lu; Yilin Li; Tong Peng; Lijie Xing; Haixi Xue; Jing Xu (Journal of Chemistry)
The waste drilling fluid was treated by a flocculant and a pH regulator. And a novel profile control agent base on waste drilling fluid (PCAWDF) was prepared using polymer, formaldehyde, resorcinol, and thiourea as raw materials under mild conditions. PCAWDF was characterized by infrared (IR) spectroscopy and scanning electron microscope (SEM). Compared with the profile control agent prepared by the recirculated water (PCARW), PCAWDF exhibited comparable or better stability, salt resistance, and viscoelasticity. The results of parallel core plugging experiments showed that the profile improvement capability of PCAWDF was stronger than that of PCARW (for 3000 mg/L: 84.6% versus 83.1%; for 5000 mg/L: 91.8% versus 90.2%). The main performance indexes of PCAWDF could meet the need of profile control for the water injection wells. The method could solve the problem of waste drilling fluid treatment in an economic and environmental way.